Pharmacist-led iodinated contrast media infusion risk assessment service - Jiang, Huiyan; Li, Yuan; Wu, Xiaoyan; Yu, Hongming; Zhang, Xin; Ge, Weihong; Yan, Simin (Frontiers in Pharmacology, 2023)
Background: With the increasing development of medical imaging, the use of iodinated contrast media has become more widespread. Adverse reactions caused by iodinated contrast media have drawn much attention. Despite this, there is still a lack of unified standards for the safe infusion process of iodinated contrast media in clinical practice both domestically and internationally. Objectives: Establishing a risk management service system to better predict the risks associated with iodinated contrast media infusion, reduce the incidence of adverse reactions and minimize patient harm. Method: From April to December 2021, a prospective interventional study was conducted at Nanjing Drum Tower Hospital in China. Establish an iodinated contrast media infusion risk management service system. Personalized risk identification and assessment were performed by a pharmacist-led multidisciplinary team before iodinated contrast media infusion. Early warning, prevention, and adverse reaction management were performed according to different risk levels during and after infusion. Results: A multidisciplinary team led by a pharmacist was established to assess the risk of infusion of iodinated contrast media. A total of 157 patients with iodinated contrast media risk factors were screened out, which prevented 22 serious adverse events and enhanced the quality of medical care. All participants expressed high satisfaction with the service provided.